THEORETICAL STUDY OF DOSES AND TYPE REAGENTS FOR REMOVAL EFFICIENCY AMMONIA NITROGEN FROM WASTEWATER - , В. А. (Municipal economy of cities (Technical science), 2013)
Based on the analysis of theoretical models of the formation of insoluble magnesium ammonium phosphate MgNH PO HO 4 4 2 × 6 Influence of dose and type of reagents for effective ness removing ammonia nitrogen from wastewater.